Daily Phisical Activity of Saami Primary School Children in Northern Norway - Bøthun, Øyvind; Zoglowek, Herbert (Revija za elementarno izobraževanje, 2018)
The primary aim of the study was to measure and compare daily physical activity among young people in the most northern part of Europe where the ethnic minority, the Saami people. The research population was 6-, 9- and 15-year old children in Saami majority municipalities (N=180). In this article, we present and discuss the results of a cross-sectional study of physical activity among children of primary school age. No significant differences were found when results were compared with the same age group throughout Norway, or in other European countries. The results in total indicate that global trends towards a comfortable, rather sluggish lifestyle will not stop, even when the local and regional conditions favour a different, more active and health-promoting lifestyle.DOI: 10.18690/rei.11.4.341-356.2018COBISS-ID: